DIFFERENCES OF DEPRESSION LEVELS IN TEMPORAL LOBE EPILEPSY AND EXTRA TEMPORAL LOBE EPILEPSY PATIENTS : CASE STUDY IN POST EPILEPSY SURGERY PATIENTS - Muhammad Rully Zen; Zainal Muttaqin; Yuriz Bakhtiar; Dimas Sindhu Wibisono (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Introduction: Depression is a common condition in epilepsy patients, especially temporal lobe epilepsy both before and after epilepsy surgery. However, not many studies have examined the depression status of patients undergoing surgery outside the temporal lobe (extratemporal resection). Differences in levels of depression between temporal lobe epilepsy (TLE) and extra-TLE patients are also not well known, so the effect of surgery on mood disorders in this group of epilepsy patients needs to be further investigated. Aim: This study aims to study whether there are differences in depression rates for TLE  and extra-TLE patients in case studies of post-epileptic surgery patients. Method: The design of this study was cross sectional by conducting research on patients with temporal lobe epilepsy (n = 29) and extra temporal epilepsy patients (n = 24) from 1999 to 2019. The study was conducted at the Hospitals in Semarang. Researchers recorded depression levels using the Beck Depression Inventory - II (BDI-II) after the patient had surgery. The collected data will be analyzed using the parametric 2 independent samples t test. Results: 53 patients who were subject were 29 TLE patients (54.7%) and 24 Extra TLE patients (45.3%). TLE patients who had normal BDI-II results were 14 patients (48.3%), mild depression by 6 patients (20.7%), moderate depression by 8 patients (27.6%) and severe depression by 1 patient (3,4%) while the Extra TLE patients showed normal results of 11 patients (45.8%), mild depression of 8 patients (33.3%), moderate depression of 4 patients (16.7%) and severe depression of 1 patient ( 4.2%). 2 independent samples t test showed insignificant results, namely p = 0.831. Conclusion: There are differences of depression level between TLE and Extra TLE cannot be confirmed, because there are many factors such as the duration of epilepsy and seizure frequency that influence patients. Multifactorial explanation for the depression in patients with TLE and extra TLE must be investigated.Keywords: TLE (Temporal Lobe Epilepsy), extra-TLE, Depression